Analisis Kualitas Instrumen Pembelajaran Project Based Learning Pada Materi Pengolahan Data Untuk Meningkatkan Motivasi Dan Hasil Belajar Siswa Kelas V Sekolah Dasar - Pipit Irawati (LPPM Politeknik Pratama, 2023)
Analysis of this learning tool is used to measure learning outcomes, especially in the learning of fifth grade mathematics information processing and thinking skills. The purpose of this study was to determine the quality and validity of a class VSD mathematics learning outcomes test instrument in data processing materials based on content validity tests. This study used a quantitative descriptive approach to study faculty, classroom teachers, and fifth graders at Dian Wakana Christian Elementary School. Validity determinations This shows that using the problem-based learning learning model leads to improved critical thinking skills when learning mathematics, with an average improvement of 22.24%.. Research has shown that all the tools and instruments used are of high quality and effective, so they can be used wisely. To improve learning outcomes. Math. Regarding data processing, especially the critical thinking aspect.